Immunnoinflammatory and profibrotic factors in pathogenesis of cardiorenal syndrome in patients with chronic heart failure and type 2 diabetes mellitus - Narizhna, Anna (My University, 2013)
For the first time it is planned to research the character of changes of pro-inflammatory and anti-inflammatory levels of the cytokine links in advance of cardiorenal syndrome in patients suffering from chronic heart failure (CHF) with or without type 2 diabetes mellitus (DM). It is planned to analyze the character of changes of the profibrotic and the anti-fibrotic markers and their role in development of kidneys dysfunction in patients suffering from CHF with or without type 2 DM. This is a new study of effects β-adrenoblockers on indices of kidneys dysfunction, fibrotic, immunnoinflammatory markers, carbohydrate and lipid exchange in patients suffering from CHF with or without type 2 DM